COVID-19 Omicron variant - Time for airborne precautions. (June 2022) - Yousaf, Zohaib; Khan, Muhammad Arslan; Asghar, Muhammad Sohaib; Zaman, Musharaf; Ahmed, Mushtaq; Tahir, Muhammad Junaid
Abstract: Genetic mutations in SARS-CoV-2 have resulted in variants with more transmissibility and partial resistance to COVID-19 vaccines, as seen in the recently classified variant of concern (VOC) "Omicron". The rapid spread has raised concerns about Omicron being airborne, which leads to a high risk of contamination in public premises, particularly among the frontline healthcare workers. Mandatory usage of protective face masks and respirators is highly recommended in order to break the chain of transmission. Furthermore, health authorities need to reassess the modes of transmission of VOCs and provide updated guidelines to the general public for its prevention.